Regulating the Electron Localization of Metallic Bismuth for Boosting CO2 Electroreduction - Wu, Dan; Feng, Renfei; Xu, Chenyu; Sui, Peng‑Fei; Zhang, Jiujun; Fu, Xian‑Zhu; Luo, Jing‑Li (Nano-Micro Letters, 2021)
Electrochemical reduction of CO2 to formate is economically attractive but improving the reaction selectivity and activity remains challenging. Herein, we introduce boron (B) atoms to modify the local electronic structure of bismuth with positive valence sites for boosting conversion of CO2 into formate with high activity and selectivity in a wide potential window. By combining experimental and computational investigations, our study indicates that B dopant differentiates the proton participations of rate-determining steps in CO2 reduction and in the competing hydrogen evolution. By comparing the experimental observations with the density functional theory, the dominant mechanistic pathway of B promoted formate generation and the B concentration modulated effects on the catalytic property of Bi are unravelled. This comprehensive study offers deep mechanistic insights into the reaction pathway at an atomic and molecular level and provides an effective strategy for the rational design of highly active and selective electrocatalysts for efficient CO2 conversion. Highlights: 1 B atoms modify the local electronic structure of Bi with positive valence sites. B doped Bi boosts highly efficient electroreduction of CO2 to formate. 2 B dopant differentiates the proton participations in CO2 RR and HER processes. 3 The dominant mechanistic pathway of B promoted formate generation is unraveled.